2006
DOI: 10.1074/jbc.m509182200
|View full text |Cite
|
Sign up to set email alerts
|

Versican G3 Domain Promotes Blood Coagulation through Suppressing the Activity of Tissue Factor Pathway Inhibitor-1

Abstract: We have detected versican, a member of the large chondroitin sulfate proteoglycans, and its degraded C-terminal G3 fragments in human plasma and observed that the versican G3 domain promoted blood coagulation. Silencing G3 expression with small interfering RNA reduced the effect of G3 on coagulation. Plasma coagulation assays suggest that G3 enhances coagulation irrespective of its actions on platelets and white blood cells. To examine how versican affected blood coagulation, we used normal human plasma and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…CD36 expression has recently been shown to be related to macrophage activation (Puig‐Kroger et al 2006), while soluble CD36 has been related to accelerated atherosclerosis in type 2 diabetes, and has been proposed to represent a marker of metabolic syndrome and a potential surrogate marker for atherosclerosis (Handberg et al 2006). The third top gene (CSPG2) codes for chondroitin sulphate proteoglycan (versican), an important protein in wound healing and tissue remodelling that was recently shown to promote blood coagulation by suppressing the activity of tissue factor pathway inhibitor‐1 (Zheng et al 2006), to be induced in infiltrated monocytes during experimental myocardial infarction in an animal model (Toeda et al 2005) and to be involved in oxidative stress‐induced apoptosis (Wu et al 2005). Similarly, the gene encoding for the integrin α M chain (ITGAM), which was also found to be down‐regulated, contributes to the formation of a leucokyte‐specific integrin that is important in the adherence of neutrophils and monocytes to stimulated endothelium and the firm adhesion and transmigration of leucokytes at sites of platelet deposition (Wang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…CD36 expression has recently been shown to be related to macrophage activation (Puig‐Kroger et al 2006), while soluble CD36 has been related to accelerated atherosclerosis in type 2 diabetes, and has been proposed to represent a marker of metabolic syndrome and a potential surrogate marker for atherosclerosis (Handberg et al 2006). The third top gene (CSPG2) codes for chondroitin sulphate proteoglycan (versican), an important protein in wound healing and tissue remodelling that was recently shown to promote blood coagulation by suppressing the activity of tissue factor pathway inhibitor‐1 (Zheng et al 2006), to be induced in infiltrated monocytes during experimental myocardial infarction in an animal model (Toeda et al 2005) and to be involved in oxidative stress‐induced apoptosis (Wu et al 2005). Similarly, the gene encoding for the integrin α M chain (ITGAM), which was also found to be down‐regulated, contributes to the formation of a leucokyte‐specific integrin that is important in the adherence of neutrophils and monocytes to stimulated endothelium and the firm adhesion and transmigration of leucokytes at sites of platelet deposition (Wang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The classic assay for whole-blood coagulation time was modified by using 12 × 75-mm polypropylene test tubes (Fisher Scientific, Suwanee, Georgia) (Zheng et al, 2006). The protocol and consent form were approved by the University of North Carolina School of Medicine Committee for the Protection of the Rights of Human Subjects.…”
Section: Whole-blood Coagulation Timementioning
confidence: 99%
“…In vivo functional studies using adenoviral over-expression of a construct that approximates proteolytically cleaved versican, i.e., the N-terminal G1 domain, demonstrated that this fragment affected myocardial cell-cell interactions differently from the V3 isoform (Kern et al, 2007). Several studies have indicted that isolated subdomains of versican can profoundly influence cell behavior (LaPierre et al, 2007; Sheng et al, 2005; Wu et al, 2004; Yang et al, 2003; Zhang et al, 1999; Zheng et al, 2006). Therefore cleavage of versican V1 may not only alter the function of intact versican, but may uncover cryptic activities of cleaved fragments (Kern et al, 2007; Kern et al, 2006; Longpre et al, 2009; Wight, 2005).…”
Section: Introductionmentioning
confidence: 99%